Experiences of mental health nurses who give nursing intervention among child and adolescent with cyberbullying: a qualitative study - Iyus Yosep; Ai Mardhiyah; Suryani Suryani; Rohman Hikmat; Kurniawan Kurniawan; Heni Purnama (BMC Nursing)
Abstract Background The incidence of cyberbullying among adolescents has been increasing significantly each year, causing negative psychological impacts such as anxiety, low self-esteem, and depression. Mental health nurses play a pivotal role in mitigating these effects and supporting adolescent victims of cyberbullying through comprehensive nursing care. Objective This study aimed to investigate the experiences of Mental health nurses in providing nursing interventions to adolescent victims of cyberbullying, focusing on challenges, strategies, and specific care practices. Methods A qualitative descriptive approach was employed, utilizing semi-structured interviews to gather data from 12 Mental health nurses working in child and adolescent rehabilitation units at a psychiatric hospital in West Java Province, Indonesia. Participants were selected using purposive sampling to ensure a diverse representation of nurses with experience in handling cases of cyberbullying. Data were analyzed thematically, with specific attention to the identification of recurring patterns and themes related to nurses’ interventions and experiences. Results The analysis identified five main themes: (1) types of bullying experienced by adolescents, (2) factors influencing the impact of cyberbullying, (3) obstacles and difficulties faced by nurses, (4) specific nursing interventions employed, and (5) unique experiences and coping strategies of nurses. Nurses underscored the challenges of addressing the multifaceted effects of cyberbullying and the importance of individualized interventions to support victims effectively. Conclusion The study highlights the critical role of mental health nurses in providing targeted, holistic care for adolescent victims of cyberbullying. Nurses emphasize the need for comprehensive care strategies, the involvement of parents, and collaboration with the adolescent’s social environment to foster positive coping mechanisms and resilience. These findings advocate for healthcare policies and training programs that empower nurses to effectively address cyberbullying and provide robust support to affected adolescents.